ANALISIS PERAMALAN PENJUALAN SEPEDA DAN MOTOR LISTRIK - Herlambang, Landung Aji; Sugianto, Welly (Computer Science and Industrial Engineering, 2021)
ABSTRAK PT Magnum Molis Batam Indonesia is a business engaged in the assembly and sale of H2, F1 E-bikes and Tricycle electric motorbikes, Tomo. PT Magnum Molis Batam is only based on estimates, resulting in frequent shortages of sales of goods and excess inventory. This research uses the research stage of the Moving Avarage Method to predict a technical analysis using factual data that exists in the past. After that, there is the forecasting. Exponential smooting method is one of the methods in forecasting the moving average with weighting where the data is weighted by a function of the Exponential Smooting Method. And the last one is the Weighted Moving Avarage Method with an average pattern that is generated by weighting, where each period is weighted, the closer to the present, the greater the weight value. PT Magnum Molis Batam Indonesia got the results of the Tricycle electric motor with the MA method: 18.6units, exponential smooting 0.1 / 0.5 / 0.9: 51.3. 34.5 -33.48 units, WMA 34 units. Tomo electric motor with MA method: 20.1 units, Exponential smooting 0.1 / 0.5 / 0.9: 43.35. 69.90.6 units, WMA 31.5. E-Bike H2 with MA method: 94.2 units, Exponential smooting 0.1 / 0.5 / 0.9: 79.28. 45. - 7,8 units, WMA 23 units. E-Bike F1 with MA method: 156.6 units, Exponential smooting 0.1 / 0.5 / 0.9: 92.7. 109.5. 135.7 units, WMA 32.5.